Community‐Based Organizations and Institutional Work in the Remote Rural West. Issue 6 (November 2015) - Abrams, Jesse; Davis, Emily Jane; Moseley, Cassandra
Abstract The institutional landscape for public land management in the U.S. West underwent a seismic shift in the 1990s as the long‐dominant resource extraction paradigm was replaced by the ecosystem management paradigm. Here we analyze the efforts of community‐based organizations (CBOs), entities that emerged in some locations across the West to help their respective communities navigate the transition from resource extraction to environmental stewardship. Despite their formal status as civil society actors, in practice CBOs came to fill various institutional gaps by taking on roles traditionally assigned to both the state and the private sector. We use a case study approach to examine how the Hayfork, California–based Watershed Research and Training Center engages in institutional work within a setting that is at once both open and constrained, as the rural community within which it operates lacks strong state‐ or industry‐led development trajectories while remaining constrained by the legacies of past institutions.